2013
DOI: 10.1136/jnnp-2013-305585
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive burden of stroke emerges even with an intact NIH Stroke Scale Score: a cohort study

Abstract: Cognitive deficits were common even in patients with the lowest NIHSS scores. Thus, low NIHSS scores are not effective indicators of good cognitive outcomes after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…A further limitation relates to the fact that we did not have information available on prestroke motor and cognitive performance. However, as previously stated, the NIHSS is relatively protected against influences by cognitive impairment, 22,23 and analyses restricted to patients with a prestroke mRS=0 did not meaningfully change our results. Together, this assuages concerns that our results were biased by preexisting deficits.…”
Section: Strokementioning
confidence: 39%
See 1 more Smart Citation
“…A further limitation relates to the fact that we did not have information available on prestroke motor and cognitive performance. However, as previously stated, the NIHSS is relatively protected against influences by cognitive impairment, 22,23 and analyses restricted to patients with a prestroke mRS=0 did not meaningfully change our results. Together, this assuages concerns that our results were biased by preexisting deficits.…”
Section: Strokementioning
confidence: 39%
“…These analyses demonstrated that infarct volume and leukoaraiosis severity were independently associated with the admission NIHSS in addition to intravenous r-tPA use (Table 2; P<0.05). Finally, although the NIHSS is relatively protected against influences by cognitive impairment, 22,23 we conducted sensitivity analyses restricted to patients with a prestroke mRS of 0 (n=206) to avoid potential confounding by preexisting functional deficits. This did not meaningfully change the results, and leukoaraiosis remained independently associated with the admission NIHSS (coefficient, 0.105; 95% confidence interval, 0.005-0.204; P=0.039; not shown).…”
Section: Multivariable Linear Regression Analysesmentioning
confidence: 99%
“…Planton and co-workers have reported a 40% overall rate of cognitive impairment 3 months post-stroke in 60 patients with good clinical outcome (defined by mRS ≤ 2 and NI-HSS ≤ 3) [22]. Furthermore, in a subgroup of stroke patients with no apparent neurological symptoms (NI-HSS = 0), Kauranen and co-workers observed cognitive impairment in 41% of patients at 1-2 weeks' evaluation and 32% of patients at 6 months' followup [23]. The patients of both these studies were younger compared to our study, which could explain their lower figures.…”
Section: Discussionmentioning
confidence: 97%
“…First, the discrepancy between similar, early neurological course and much poorer subsequent outcome in older as compared with younger patients had two main aspects: (a) a lower likelihood of achieving functional independence (mRS 0–2) in spite of similar early NIHSS scores, and (b) a high overall (delayed) mortality in contrast to similarly low early death rates. While the former (a) may be largely explained by factors such as pre-existing functional impairments, stroke-induced cognitive deficits (which may be under-rated by NIHSS scores29), and limited functional restoration capacities of the damaged ageing brain, such mechanisms are unlikely to account for (b), which is more plausibly explained by the relatively high prevalence of post-stroke complications and comorbidities in older patients. Second, and in line with this, none of even the three early fatalities in the older patients was directly linked to stroke-related brain damage (all three were due to medical complications), whereas five of eight early deaths in the younger patients were directly related to malignant infarction or SICH.…”
Section: Discussionmentioning
confidence: 99%